Pharmacological Screening of Polyherbal Formulation for Hepatoprotective Activity on Albino Rats - Fathima, Ayesha; Nawaz, Sabha; Begum, Sofia; Maryam, Syeda; Fasahath, Syeda Adida; Begum, Zareena; S, Roshan.; Mahammed, N. L. (Asian Journal of Pharmaceutical Research and Development, 2015)
The present study was designed to evaluate hepatoprotective activity of poly herbal formulation (Andrographis paniculata, Boerhaavia diffusa, Eclipta alba, Picrorhiza kurroa) in Wistar albino rats using carbon tetra chloride (CCL4) induced hepatic damaged experimental animals.carbon tetra chloride (CCL4 ) (1ml/kg, i.p) was administered a single dose to induce hepatotoxicity. Poly herbal formulation (200 mg/kg, p.o,400 mg/kg, p.o,) and liv-52 syrup (50ml/kg, p.o.) were administered once daily for 8 days. The degree of hepatoprotection was measured using morphological parameters of changing in colour and weight of liver are determined. Biochemical parameters in serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), serum alkaline phosphatase (SALP), bilirubin and plasma protein. The histopathological parameters of histological changes in the liver architecture like architecture of hepatic lobules, swelling of liver cell, fatty changes, focal necrosis, inflammatory cell infiltration around portal areas, kupffer cell hyperplasia etc. and the functional parameters of pentobarbitone sleeping time was used as a functional parameter.PHF(poly herbal formulation) pretreatment showed normal morphological parameters signs and significant effect of serum enzymes, total protein and bilirubin levels.Highly significantly protect the hepatic damage and morphological and histopathological changes and less pentobarbitone sleeping time were observed in all the three poly herbal formulations treated rats.The result of this study strongly indicated that the poly herbal formulation has got a hepatoprotective action against carbon tetra chloride (CCL4) induced hepatic damage in experimental animals.